Applied Philology of Professional Activity of the Future Teacher - Nematjonovna, Mamatova Shakhnoza; Yuldashevna, Khaydarova Gulbahor (Journal of Medical Genetics and Clinical Biology, 2024)
The article discusses the system of communicative-oriented courses that has developed in the practice of the author's work with students studying applied philology, providing competencies in the field of professional rhetoric, culture of speech and media literacy.